Remote monitoring of gas pipelines on the basis of magnetic elastic sensors of mechanical voltage - Tsyganchuk, V. V.; Shlapak , L. S.; Matviienkiv , O. M.; Sydor , P. Ya. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
A method of controlling the stress state of gas pipelines with a four-pole magnetoanisotropic converter has been suggested. The Arduino hardware and software platform has been used to enhance the capabilities of the INI-1C basic mechanical stress measuring device. The system of remote monitoring for periodic measurements of pipeline voltages, accumulation and analysis of the received data has been described in order to provide objective information for making technological decisions.